2011
DOI: 10.1080/10942910903243673
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties, Phenolic Contents and Antioxidant Activity of Sudanese Honey

Abstract: The physicochemical properties, antioxidant activities and phenolic contents of seven types of Sudanese honeys derived from flowers of Acacia nilotica, Acacia seyal, Azadirachta indica, Cucurbita maxima, Balanites aegyptiaca, and two Ziziphus spina christi plant species were evaluated. The moisture content was in the range from 16.2 to 21.3, g/100 g honey, ash content from 0.121 to 1.205 g/100 g honey, nitrogen from 0.032 to 0.046 g/100 g honey while the corresponding protein content was 0.200 to 0.286 g/100 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…The moisture of the studied honey samples was within the standards (not more than 20%) (Codex Alimentarius Commission, 2001; European Community, 2004), except the Ziziphus honey (S10) with a moisture values of 20.2%. This value is similar to the Moroccan Ziziphus honey (Aazza, Lyoussi, Antunes, & Miguel, 2014) and higher than the Sudanese and Algerian Ziziphus honeys (Idris, Mariod, & Hamad, 2011; Zerrouk, Seijo, Escuredo, & Rodríguez‐Flores, 2018), which explain the governance of the environmental conditions on determining this parameter. 16.9% was the minimum value, seen in the case the sample S4.…”
Section: Resultssupporting
confidence: 60%
“…The moisture of the studied honey samples was within the standards (not more than 20%) (Codex Alimentarius Commission, 2001; European Community, 2004), except the Ziziphus honey (S10) with a moisture values of 20.2%. This value is similar to the Moroccan Ziziphus honey (Aazza, Lyoussi, Antunes, & Miguel, 2014) and higher than the Sudanese and Algerian Ziziphus honeys (Idris, Mariod, & Hamad, 2011; Zerrouk, Seijo, Escuredo, & Rodríguez‐Flores, 2018), which explain the governance of the environmental conditions on determining this parameter. 16.9% was the minimum value, seen in the case the sample S4.…”
Section: Resultssupporting
confidence: 60%
“…This indicates that gelam honey has high antioxidant activity. The variations in the IC 50 values of the honeys might be due to the differences in the phenolic contents and different types of phenolic compounds present [15] since each phenolic acid has different scavenging activity. [73,77] All tested stingless bee honeys showed IC 50 values lower than those of Apis mellifera honey (83.28 mg/mL) except for the acacia honey (97.24 mg/mL) from Geniotrigona thoracica and the starfruit honeys from both species.…”
Section: Antiradical Scavenging Activity (Ic 50 )mentioning
confidence: 99%
“…Thus, the antioxidant capacity in honey is attributed to the synergistic effect of a wide range of compounds including phenolics, flavonoids, products of the Maillard reaction, enzymes, organic acids and other minor compounds. [15] The antioxidant activity of honeys has been reported to have a correlation with phenolics, flavonoids, products of the Maillard reaction, ascorbic acid, organic acids, enzymes, carotenoids, amino acids, proteins and mineral content. [16][17][18] Honey has often been reported to have potential antioxidant activity, which is beneficial for human health.…”
mentioning
confidence: 99%
“…18 Briefly, various concen S85 buckwheat species. Earlier reports also revealed that TPC of tartary buckwheat was much higher than that of cranberry, apple, 26 raspberry, 27 honey, 28 corn, wheat, oats and rice 29 suggesting that tartary buckwheat may serve as an excellent dietary source of phenolics. Earlier studies have also reported that the TPC and TFC of the plants are influenced by environmental factors as well as the type of species.…”
Section: Dpph Assay (1 1-diphenyl 1-2-picryl-hydrazyl)mentioning
confidence: 92%